Modeling multicriteria group decision making as games from enhanced pairwise comparisons - Alexandre Bevilacqua Leoneti; Luiz Flávio Autran Monteiro Gomes (Operations Research Perspectives, 2021)
This research aimed to replace the pairwise comparison function used in Leoneti [2016] with a new function inspired on the exponential model of prospect theory and to perform a comparative analysis to verify the hypothesis that a better performance of the utility function would be possible from the use of a component of judgment better theoretically grounded. A field study consisting of solving three cases in a group was proposed to evaluate the number of matches of the method regarding the decision negotiated by the group, and the number of times that, when there was a match, the group maintained its decision after voting. From an empirical evaluation with a hundred students that participated in the field study, the main hypothesis of this research was confirmed, which is that the use of a pairwise comparison function adhering to a decision and judgment theory increases the predictive capacity of the utility function proposed in Leoneti [2016].
Additional information: Corrigendum available to "Modeling multicriteria group decision making as games from enhanced pairwise comparisons" [Operations Research Perspectives 8 (2021) 100194]: https://doi.org/10.1016/j.orp.2022.100239
Keywords: 330; Utility function; Prospect theory; Game theory; Nash equilibrium